Hubungan Golongan Darah Orang Tua dan Anak dengan Metode Slide - Sultan Rafi Pratama; Defi Nurul Hayati; Intan Nuraeni; Faesa Alya Fadillah; Regina Putri Nuari; Reva Rahma Sahara; Aliya Mar Atussalikhah; Griselda Clarissa Naila (Pelantar Press, 2026)
Blood group examination is an important procedure in blood transfusion practice to prevent fatal hemolytic reactions. The ABO and Rhesus blood group systems are genetically inherited following Mendelian laws. This study examined the relationship between parental blood groups and blood groups of Medical Laboratory Technology students at Muhammadiyah University of Purwokerto through slide method examination. A descriptive analytic design with a cross-sectional approach was used. The population was students using purposive sampling technique. Blood group examination was carried out using the slide agglutination method with antisera reagents A, B, AB, and D. Data were analyzed using Chi Square test with a significance level of 0.05. The distribution of student blood groups was found to be O 20 people (37.0%), B 18 people (33.3%), A 11 people (20.4%), and AB 5 people (9.3%). The Chi Square test results showed no significant relationship between father's blood group and students (p=0.080), but there was a significant relationship between mother's blood group and students (p=0.000). This study found that student blood groups are more influenced by mother's blood group than father's. It is recommended that students know their blood type as important medical data for blood transfusion and organ transplantation purposes.